2009
DOI: 10.1007/s11409-009-9041-9
|View full text |Cite
|
Sign up to set email alerts
|

Epistemic profiles and metacognition: support for the consistency hypothesis

Abstract: Relations were examined between epistemic profiles, metacognition, problem solving, and achievement in the context of learning in an educational psychology course. Two hundred thirty-one university students completed self-report inventories reflecting their epistemic profiles and use of metacognitive strategies, and were epistemically profiled as rational, empirical, or both rational and empirical in their approaches to knowing. From the larger sample, 78 students participated in a problem-solving session usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 41 publications
5
50
0
3
Order By: Relevance
“…Some theorists view SRL as a subordinate component of metacognition whereas others regard SRL as a super-ordinate to metacognition (Veenman, Van Hout-Wolters, & Afflerbach, 2006). In line with Muis and Franco (2010), the present study explores metacogniton from a regulation of cognition perspective, situated as a subordinate to SRL.…”
Section: Relevant Srl Concepts For Student Teachers' Academic Successmentioning
confidence: 79%
“…Some theorists view SRL as a subordinate component of metacognition whereas others regard SRL as a super-ordinate to metacognition (Veenman, Van Hout-Wolters, & Afflerbach, 2006). In line with Muis and Franco (2010), the present study explores metacogniton from a regulation of cognition perspective, situated as a subordinate to SRL.…”
Section: Relevant Srl Concepts For Student Teachers' Academic Successmentioning
confidence: 79%
“…Results from other research have indicated that students' epistemic beliefs may be linked to their use of self-regulatory strategies Dahl et al 2005;Muis and Franco 2009;Ryan 1984;Schommer 1990). A mechanism for this linkage suggested by Muis (2007) is that beliefs about knowledge and knowing activated as part of cognitive and affective conditions in phase one of self-regulated learning may affect task definition during this phase.…”
Section: Personal Epistemology and Self-regulated Learningmentioning
confidence: 98%
“…Based on two influential models (Pintrich 2000;Winne and Hadwin 1998) from the literature on self-regulated learning, Muis (2007) suggested four phases of regulation: a) task definition, b) planning and goal setting, c) enactment, and d) evaluation (see also, Muis and Franco 2009). In the first phase, the learner's perception of the task is generated, with contextual, cognitive, and affective conditions contributing to this process.…”
Section: Self-regulation and Computer-based Learningmentioning
confidence: 99%
“…In line with Muis and Franco (2010), the empirical studies of Stijnen (2012a, 2012b) explored metacogniton from a regulation of cognition perspective (see Section 2.1), situated as a subordinate to SRL. The empirical studies of Stijnen (2012a, 2012b) were conducted in educational theory courses containing lectures, lessons and moments of guidance.…”
Section: The Learner: Metacognition Motivation and Academic Performancementioning
confidence: 99%